Marketing research : text and cases - Boyd, harper W.; Westfall, Ralph; Stasch, Stanley F. (Delhi : A.I.T.B.S., 1999)
Business
Keywords: Marketing research; Research process; Data collection; Data analysis; Product research; Advertising research